2006
DOI: 10.1128/jb.01021-06
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection on Transposase Genes of Insertion Sequences in the Crocosphaera watsonii Genome

Abstract: Insertion sequences (ISs) are mobile elements that are commonly found in bacterial genomes. Here, the structural and functional diversity of these mobile elements in the genome of the cyanobacterium Crocosphaera watsonii WH8501 is analyzed. The number, distribution, and diversity of nucleotide and amino acid stretches with similarity to the transposase gene of this IS family suggested that this genome harbors many functional as well as truncated IS fragments. The selection pressure acting on full-length transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
(40 reference statements)
2
10
1
Order By: Relevance
“…The IS density among Ensifer species was highly correlated to the number of items identified in COG class L observed from functional genomics analyzes and explain the variability observed in this particular class (data not shown). These results suggest that in comparison to other species studied here, E. aridi strains possess a lower diversifying agent potential which could limit their adaptation to other ecological niches [61, 62]. However, we found in the genomes of E. aridi that predicted prophage regions were mainly incomplete and intact prophage regions were only identified in the Indian strains suggesting a more recent transfer in Asian isolates.…”
Section: Resultscontrasting
confidence: 48%
“…The IS density among Ensifer species was highly correlated to the number of items identified in COG class L observed from functional genomics analyzes and explain the variability observed in this particular class (data not shown). These results suggest that in comparison to other species studied here, E. aridi strains possess a lower diversifying agent potential which could limit their adaptation to other ecological niches [61, 62]. However, we found in the genomes of E. aridi that predicted prophage regions were mainly incomplete and intact prophage regions were only identified in the Indian strains suggesting a more recent transfer in Asian isolates.…”
Section: Resultscontrasting
confidence: 48%
“…It has been hypothesized that genetic diversity in C. watsonii may be maintained by genome rearrangement, rather than by gene sequence divergence because the diazotroph has low levels of genome DNA sequence variability between habitats and over time (Zehr et al, 2007a). High transposase activity in C. watsonii is similar to that found in populations of the archaeon Ferroplasma acidarmanus (Allen et al, 2007), and positive selection of transposases has been linked to increased fitness or invasion of new environments (Mes and Doeleman, 2006;Allen et al, 2007;Franguel et al, 2008). The C. watsonii WH8501 genome has a large number of transposases (419 transposases in the B6.3 Mb genome), some of which interrupt reading frames of genes (Zehr et al, 2007a) and may result in phenotypic diversity.…”
Section: Resultsmentioning
confidence: 63%
“…). Initial genomic studies found that cultivated and wild Crocosphaera genomes had unusually high numbers of transposases, suggesting a mechanism for adaptation to changing environmental conditions and establishment of the variety of phenotypic differences between strains (Mes and Doeleman , Zehr et al. , Hewson et al.…”
Section: Free‐living Unicellular Nitrogen‐fixing Cyanobacteriamentioning
confidence: 99%